Students Perspective on Online Learning During Covid -19 at Rural Area Thailand - Marianne Putri Talimbekas; Yudhi Arifani (Institut Agama Islam Negeri Palopo, 2022)
The main reason for this exploratory study was to identify the general mentality of Thai high school. Students en route to mandatory virtual learning process amid coronavirus (COVID-19). The sample exam included 130 2nd school students for the 1st school, which included three different grades namely M1 (32 students), M2 (34 students) and M3 (30 students). And also the second school (30 students). An online survey method was used to collect information on Thai high school students'' perspectives on internet education. The 10-item questionnaire was used to assess the effectiveness of online learning. A pilot test of the survey was conducted among students at Ban Nonsawan School in Loei & Sansern Islam School in Songkhla,Thailand. The majority Secondary education students surveyed have doubts about online/digital learning. Lack of access to internet facilities, lack of proper interaction and contact with students and teachers, and inefficient technology are some of the biggest challenges faced by high school students in Thailand. Especially in rural schools.